2018
DOI: 10.29252/rap.8.17.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-Arginine on Productive Performance, Egg Quality Parameters, Blood and Hormone Parameters of Laying Hens in Late-phase of Production

Abstract: This experiment was conducted to investigate effects of l-arginine on productive performance and egg quality parameters, blood and hormone parameters of laying hens in late phase of production for 8 weeks. Forty eight Hy-Line W-36 were used in a completely randomize design with four level of l-arginine (1/20=control diet, 1/32, 1/44 and 1/56 percent) and four replicate from 92-98 weeks of age. Layers were weighed at 90 week of age and randomly distributed into 16 cages in order to have a similar pen body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Additionally, these researchers showed that L-carnitine supplementation had no significant effect on yolk index and yolk color score. Kazemi-Fard et al, (2015) did not find any significant impact on egg yolk, yolk color, and yolk quality index in hens fed a diet containing 50 mg/kg of Lcarnitine compared to hens on a control diet. The study also found a significant interaction (p≤0.01) between the addition of LC and lines on yolk weight, yolk diameter, yolk index, and yolk/albumen ratio, while yolk height and yolk percentage were not significantly affected by Lcarnitine supplementation.…”
Section: :5: Egg Yolk Parametersmentioning
confidence: 55%
See 2 more Smart Citations
“…Additionally, these researchers showed that L-carnitine supplementation had no significant effect on yolk index and yolk color score. Kazemi-Fard et al, (2015) did not find any significant impact on egg yolk, yolk color, and yolk quality index in hens fed a diet containing 50 mg/kg of Lcarnitine compared to hens on a control diet. The study also found a significant interaction (p≤0.01) between the addition of LC and lines on yolk weight, yolk diameter, yolk index, and yolk/albumen ratio, while yolk height and yolk percentage were not significantly affected by Lcarnitine supplementation.…”
Section: :5: Egg Yolk Parametersmentioning
confidence: 55%
“…Similar results were found by Rizk et al,(2022) found that adding L-carnitine (300 and 450 mg/kg food) to the broiler diet significantly increased (P≤0.05) egg laying compared to the control diet. However, Corduk and Sarica, (2008); Kazemi-Fard et al, (2015) concluded that dietary intake of 100 and 150 mg/kg L-carnitine increased egg production in laying hens by 7.81 and 10.74%, respectively, because this additive (L-carnitine) improves lipolysis and liver protection. Neuman et al, (2002) found that Lcarnitine supplementation increased mitochondrial energy production and in turn, laying intensity in these birds.…”
Section: Hen Day Egg Production (Hd%)mentioning
confidence: 99%
See 1 more Smart Citation